Thermal, mechanical and tribological properties of polycarbonate/acrylonitrile-butadiene-styrene blends - Khun, Nay Win. (2013)
Polycarbonate (PC) and acrylonitrile-butadiene-styrene (ABS) were blended by varying ABS content. The thermal, mechanical and tribological properties of the PC/ABS blends were systematically characterized. Increasing ABS content in the PC/ABS blends decreased thermal stability of the blends, as a result of the lower thermal stability of the ABS than that of the PC. Although the tensile strength of the PC/ABS blends apparently decreased with increased ABS content, the PC/ABS blend with 10 wt% of ABS had the highest tensile strength, because of improved processability of the blend. The friction and wear of the ABS measured against a steel ball of 6 mm in diameter were higher than those of the PC. As a result, a higher ABS content in the PC/ABS blends resulted in higher friction and wear of the blends. The scratch results showed that scratching with a 5 mm steel ball generated a scratch with a shorter length and lower depth on the PC than on the ABS, which indicated better scratch resistance of the PC. Therefore, the PC/ABS blend with 50 wt% of PC had better scratch resistance than the ABS, due to the influence of the PC embedded in the blend.